Anthropometric profile of advanced swimmers and the biomechanics of swimming - Rejman, M.; Bornikowska, A.; Tyc, L.; Kociuba, M.; Rudnik, D.; Koziel, S. (XIII th International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2018)
The aim of research was to compare the anthropometric indicators and parameters of skilled adult swimmers and students who have never undertaken swimming training. Two groups of men, homogeneous in age (18-25 years) and sociotechnical criteria, took part in the research. Swimmers (n=28) specializing in various strokes at 100 and 200 m represent the high level of proficiency. The control group (n=28) consisted of physical education students. In both groups direct anthropometric measurements (body height, length, width and depth, and circumference of its segments) were made. Additionally, non-standard parameters, such chest depth, hand length, palm width, hand width, distal forearm epiphysis width, elbow epiphysis width, knee epiphysis width, ankle and foot width were collected. Moreover, 14 anthropometric indices were proposed. The anthropometric profile was constructed on the basis of normalized mean values and defined a set of 27 parameters and indices significantly differentiating the professional swimmers from the control group (test t-student). Accordingly, some previously unidentified somatic traits of swimmers were identified: a relatively longer shank (difference in knee length-to-lower limb ratio (+6.6 cm)); a slim, elongated shape of the hand (difference in palm breadth-to-hand length ratio (-2.1 cm)); and a slim foot difference in foot breadth-to-foot length ratio (-1.2 cm)). The identified intergroup differences in the somatic body composition of swimmers and their reference to the laws of biomechanics and hydrodynamics give the results a contributing dimension, to reinforce the thesis, that anthropological characteristics may be helpful in identifying factors favouring progression in swimming performance.